Electronic medical record‐verified hepatitis C virus screening in a large health system - Monica L. Kasting (Cancer Medicine, 2019)
Abstract Background Baby boomers are at increased risk for hepatitis C virus (HCV) infection and related cancer; therefore, one‐time HCV screening is recommended. Methods To assess prevalence of, and factors associated with providers ordering HCV screening, we examined a retrospective cohort of electronic medical records for patient visits from 01 August 2015 until 31 July 2017 in a large health system. HCV screening ordered was examined by patient age, gender, race/ethnicity, provider specialty, and number of clinical visits, stratified by birth cohort: born ≤1945, 1945‐1965 (baby boomers), 1966‐1985, and ≥1985. Multivariable regression identified factors independently associated with HCV screening ordered among average risk baby boomers. Results A total of 65 114 patients ages ≥18 years were evaluated. Among baby boomers HCV screening test order increased threefold between the two study years (4.0%‐12.9%). Odds of screening test ordered were significantly higher for non‐Hispanic Blacks (multivariable adjusted odds ratio [aOR]=1.36; 95% CI = 1.19‐1.55), males (aOR = 1.44; 95% CI = 1.33‐1.57), and having a clinic visit with a primary care provider alone or with specialty care (aOR = 3.25‐4.16). Medicare (aOR = 0.89; 95% CI = 0.80‐0.99), Medicaid (aOR 0.89; 95% CI 0.80‐0.99), and an unknown provider type (aOR = 0.16; 95% CI = 0.08‐0.33), were associated with lower odds of screening tests ordered. Conclusions While the proportion of baby boomers with an HCV screening test ordered increased during the study, the rate of screening remains far below national goals. Data from this study indicate that providers are not ordering HCV screening universally for all of their baby boomer patients. Continued efforts to increase HCV screening are needed to reduce the incidence of HCV‐related morbidity and mortality.